Lijden en Dood 1. (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1989)
Bolle, Jos ; Derore, Joel ; Devreux, Pierre ; Dubois, Danny ; Ledent, Ingrid ; Lemmens, Dirk ; Lens, Gilbert ; Maieu, Frank ; Moriau, Rik ; Niels, Eddy ; Reniere, Paul ; Szymkowicz, Charles ; Vandercam, Serge ; Van Wynendael, Sylvain ; Vreven, Flor
Lijden en Dood 1, Nederloo, Sint-Pieters-Leeuw, 24 november 1989 - 7 januari 1990
boek